Use of radium in studying water resources in Shanafiya-Samawa areasouth Iraq - K. Ali, Kamal; R. Ajina, Ali (Iraqi Journal of Science, 2023)
The water resources, Groundwater and surface water, in Shanafiya – Samawaarea- southern Iraq were investigated using radium-226. The study examines the useof radium as tracer whether saline surface water (Sawa Lake) seeps and interactswith water of the Euphrates River and where groundwater interacts with surfacewater, Euphrates, Atshan River and Sawa Lake. As well as examine the radiologicaldoses caused by consumption of these waters. Thirteen water samples were analysisfor radium-226 content by precipitation with barium carrier by using gammaspectroscopy based on hyper-pure Germanium with efficiency 30%. The resultshows that Sawa Lake contains radium concentration higher than that ofgroundwater and other sources of surface water. The high value of Ra in the SawaLake can be related to the high salinity. Groundwaters generally have Raconcentrations that broadly correlate with salinity or with total dissolved solids(TDS). The radium content in the different water depends on the hydrochemistry ofwater especially chlorine and TDS. The radium contents accumulate as clusters indifferent groups when plotted with chlorine and TDS which reveals no intermixingbetween the different water resources. While the relatively high concentration of Ra-226 in Sawa Lake may be caused by accumulation of Ra by maxing withgroundwater according the hypotheses that states: in high salinity water system thedissolution of radium increases and accumulates in the solution. While low Ra-226concentration in river water reveals that no intermixing has occurred betweengroundwater and river water. The annual effective doses due to ingestion ofgroundwater and river water in the study area were estimated to be less than thevalues recommended by IAEA and WHO.